Shiva linga in the Garbhagriha of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Hazareshwar Temple, also known as the Swarnajaleshwar Temple, houses a Shiva linga in the garbhagriha (sanctum sanctorum). This linga is positioned on a square yonipatta (womb-shaped base) and intricately carved with numerous smaller lingas. It is this unique feature of the linga, adorned with hundreds and thousands of lingas, that lends the temple its name, the Hazareshwar Temple.